Honouring and incorporating diverse Indigenous decision-making traditions - Lightbourn, Ryleigh (Research Partnerships and Knowledge Mobilization, 2020)
Bill C-92: An Act respecting First Nations, Inuit and Métis children, youth and families confirms the jurisdiction of Indigenous communities over children and family services. Honouring and incorporating Indigenous decision-making traditions in co-developed processes for services is an important step towards supporting the principles of Bill C-92 and working towards reconciliation. Graduate Unreviewed